Association of contact history and family behavior with tuberculosis in children at Banyu Urip Public Health Center, Surabaya City, Indonesia: A case-control study - Agustin, Avita Fitri Agustin; Sulistyorini, Lilis (Universitas Udayana, 2023)
Background and purpose: The Surabaya City had the highest number of pediatric tuberculosis cases in East Java Province; while, Banyu Urip Public Health Center contributed significantly to the number of pediatric tuberculosis in Surabaya. This study aims to analyze risk factors of tuberculosis among children aged 0-14 years in the working area of the Banyu Urip Public Health Center in Surabaya City. Methods: This is a case-control study conducted in Banyu Urip Public Health Center area in 2022. All 42 children aged 0-14 years with TB were included as cases and 42 healthy children were selected as control purposively. Data collection was carried out using questionnaires which filled in by the guardian/caregiver of each child. The variables collected include children’s characteristics, immunization history, contact history and knowledge, attitude, practices (KAP) toward TB of the families. The data was analyzed descriptively and continued with a Chi-square test. Results: The majority of children had received BCG immunization among both cases (95.2%) and control (100%) and had no comorbidities among cases (88.1%) and control (97.6%). We found history of contact (p<0.001), poor families’ knowledge (OR=3.80; 95%CI: 1.00-17.56; p=0.0026) and poor practices (OR=3.28; 95%CI: 1.22-8.92; p=0.009) were associated with a higher likelihood of TB infection among children in Surabaya. Conclusion: Risk factors for pediatric TB were contact history with TB patients, poor family knowledge, and poor family practices. Awareness campaign to improve parental and community knowledge and practices regarding TB must be carried out using different methods that are preferred by the communities.